2017
DOI: 10.1002/ijc.30696
|View full text |Cite
|
Sign up to set email alerts
|

Employment status and occupational level of adult survivors of childhood cancer in Great Britain: The British childhood cancer survivor study

Abstract: The British Childhood Cancer Survivor Study (BCCSS) provides the first detailed investigation of employment and occupation to be undertaken in a large population‐based cohort. Previous studies have been limited by design issues such as using small numbers of survivors with specific diagnoses, and involved limited assessment of employment status and occupational level. The BCCSS includes 17,981 5‐year survivors of childhood cancer. Employment status and occupational level were ascertained by questionnaire from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 28 publications
(79 reference statements)
2
56
1
Order By: Relevance
“…Studies of the employment status of survivors of a broad range of childhood cancers in comparison with the general population or sibling comparisons had inconsistent findings . Seven studies observed higher unemployment rates among survivors, whereas five studies found similar unemployment rates . Studies with stratification by type of unemployment found that survivors were more likely to be unemployed due to illness or disability .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies of the employment status of survivors of a broad range of childhood cancers in comparison with the general population or sibling comparisons had inconsistent findings . Seven studies observed higher unemployment rates among survivors, whereas five studies found similar unemployment rates . Studies with stratification by type of unemployment found that survivors were more likely to be unemployed due to illness or disability .…”
Section: Resultsmentioning
confidence: 94%
“…Seven studies observed higher unemployment rates among survivors, whereas five studies found similar unemployment rates . Studies with stratification by type of unemployment found that survivors were more likely to be unemployed due to illness or disability . A study in North America reported that survivors were six times more likely to be unemployed for health reasons than their siblings (10.4% vs .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, TBI has a known association with debilitating long-term complications such as endocrinopathies, and end-organ damage 18 . Similarly, the studies focusing on cancer survivors have consistently shown negative effects of radiation, especially cranial radiotherapy on employment outcomes 1315 . Cranial radiation has also been shown to affect educational outcomes in long-term survivors of childhood cancer 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on employment outcomes in adult survivors of childhood cancer who did not undergo HCT have also shown that younger age at diagnosis was associated with decreased likelihood of being employed. Frobisher and colleagues studied the employment and occupational status of pediatric cancer survivors using the British Childhood Cancer Survivorship Study (BCCSS) 13 . Compared to the general population, survivors were less likely to be employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation